2019
DOI: 10.1177/0958305x18813684
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thermal and solar performance in atrium buildings using sequential simulation

Abstract: Nowadays complex atrium design is becoming popular in city skylines that bring natural lighting to create more pleasant indoor environment. Atriums with complex skylight design and lack of knowledge in building thermal performance in relation to transmitted solar radiation through skylight contribute to greenhouse effect. This has imposed high-energy consumption for cooling load particularly in warm humid regions. In order to obtain good thermal performance of atrium with appropriate skylight design, scholars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Since atria generally suit cold and temperate climates, hot climates with high solar radiation are challenging. In the tropics, atria with side-lit skylights are mostly recommended [11,[15][16][17][18][19][20][21][22][23][24].…”
Section: Atrium Design and Thermal Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Since atria generally suit cold and temperate climates, hot climates with high solar radiation are challenging. In the tropics, atria with side-lit skylights are mostly recommended [11,[15][16][17][18][19][20][21][22][23][24].…”
Section: Atrium Design and Thermal Performancementioning
confidence: 99%
“…In the tropics, Moosavi (2015) tested different passive strategies in a multi-storey atrium with a southern facade, and concluded that operating natural ventilation decreased the indoor temperatures and humidity levels [22]. Ab Ghafar and others (2019) tested different materials and forms of atrium skylights; the study concluded that the northern and more inclined skylight consumes less energy [11]. Another study tested a lateral atrium with double-skin facade and concluded that atrium thermal performance can be improved by the openings' size and position design [43].…”
Section: Atrium Thermal Pefrormancementioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] In particular, the integration of renewable energy sources into smart buildings, smart sites and smart home concepts have gained importance; the studies examining the performance of integration and offering different energy management systems to increase performance have also gained importance. [10][11][12][13][14][15][16] Lee et al 14 analyzed the overall utilization potential of BIPv/Wt system for 143 cities at a different global region. Buonomano et al 15 considered a hybrid renewable energy system contains photovoltaic panels and wind turbine with an energy storage system.…”
Section: Introductionmentioning
confidence: 99%
“…At this point, the height of the building varies according to parameters such as glazing type and climate type. Ghafar et al [18] tested the thermal performance of 5 different atrium types for 4 different climate types according to different skylight positions and tilted angles using 2 simulation programs (to ensure the accuracy of the results). And then calculated the solar intensities for different roof geometries.…”
Section: Introductionmentioning
confidence: 99%